(untitled) (Revista Contexto & Educação, 2026)
This article aims to identify the contributions of Vygotsky and Benjamin to Brazilian theses on Early Childhood Education in Brazil, focusing on “interactions,” one of the pillars of the National Curriculum Guidelines for Early Childhood Education. The research methodology used was qualitative, exploratory in nature, and classified as bibliographic research with a corpus of eight theses. Content analysis was selected for data analysis. The results showed that, even when inserted in different historical and epistemological contexts, the theories of Vygotsky and Benjamin converge on issues related to understanding interactions in Early Childhood Education. Interactions, with a focus on Vygotsky and Benjamin, reveal children as active and social beings who learn through their bodies, language, and imagination. Both authors express to the reader that knowledge construction occurs through interactions.